2011
DOI: 10.1073/pnas.1115675108
|View full text |Cite
|
Sign up to set email alerts
|

Genetically distinct coelacanth population off the northern Tanzanian coast

Abstract: Since the sensational discovery of a living coelacanth off the east coast of South Africa, the geographic distribution of viable coelacanth populations has been a subject of debate. In the past, the coelacanths off the African mainland were thought to be strays from the Comoros because most coelacanths captured were caught in the waters surrounding the Comoros archipelagos. However, in recent years, a large number of coelacanths were captured off the coast of Tanzania, including nine living specimens observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 27 publications
(36 reference statements)
1
28
2
Order By: Relevance
“…First, we constructed the reference coelacanth draft genome from one of the Tanzanian specimens (TCC041-004, gender unknown) (Nikaido et al 2011), which was recovered from the body cavity of its mother (coelacanths give birth to fully formed offspring) (Fig. 2).…”
Section: Assembling the Coelacanth Genomementioning
confidence: 99%
See 1 more Smart Citation
“…First, we constructed the reference coelacanth draft genome from one of the Tanzanian specimens (TCC041-004, gender unknown) (Nikaido et al 2011), which was recovered from the body cavity of its mother (coelacanths give birth to fully formed offspring) (Fig. 2).…”
Section: Assembling the Coelacanth Genomementioning
confidence: 99%
“…In addition to the Comoros archipelagos, several coelacanths have been captured off the coasts of Mozambique (Schliewen et al 1993), Madagascar (Heemstra et al 1996), Kenya (De Vos and Oyugi 2002), and Tanzania (Sasaki et al 2007). Nikaido et al (2011) recently demonstrated that a coelacanth population off the northern coastal region of Tanzania is genetically distinct from that of Comoros, indicating that the northern coastal region of Tanzania is the second habitat of coelacanths in the western Indian Ocean. Furthermore, two coelacanth individuals (L. menadoensis) were also captured off the coast of Manado, Sulawesi, Indonesia (Erdmann et al 1998), on the opposite side of the Indian Ocean (the locations of the captured and observed coelacanths are summarized in Fig.…”
mentioning
confidence: 99%
“…The first study [11] concluded that the low allelic diversity is the result of a small population size and the absence of strong geographic isolation, as has been concluded for similar findings in other species [14]. In contrast, the more recent study, Lampert et al [7], rejected these straightforward hypotheses.…”
Section: Low Molecular Diversity and Low Geographic Differentiation Imentioning
confidence: 84%
“…Two population genetics studies in Latimeria chalumnae are available and both show low allelic diversity and low levels of geographic differentiation [7,11]. For neutral alleles, diversity depends on two opposite forces, the rate of mutation that is the source of new alleles and the genetic drift that eliminates alleles.…”
Section: Low Molecular Diversity and Low Geographic Differentiation Imentioning
confidence: 99%
“…However, recent population genetic studies revealed genetic divergence between individuals among and within the field sites and thus a potential for adaptation in L. chalumnae 18,19 . Still they present an opportunity to get fascinating insights into the ecology and behaviour of a very old animal group.…”
mentioning
confidence: 99%